How (absent) fans influenced football during the COVID 19 pandemic? - Arrondel, Luc; Duhautois, Richard; Françon, Baptiste (Frontiers in Behavioral Economics, 2024)
The fact that home football teams win more games than away teams has been largely discussed in the literature. Crowd factors appear to be the most dominant cause of this home advantage. At the end of the 2019–2020 season, the COVID-19 pandemic forced European football teams to close their stadium to fans, allowing researchers to exploit this natural experiment to analyze the effects of crowd on match outcomes and referees' decisions. To answer to this question, we used match data played in the top two divisions of four of the main national professional leagues in European countries and Portugal in the 2018–19 and the 2019–20 seasons. We find that the total absence of a generally supportive crowd has a significant effect on home advantage. This results in a reduction of the chances of a home win, a poorer performance by the home team's players, and more severe refereeing decisions toward the home team and less severe toward the away team.